2009
DOI: 10.1055/s-0029-1220692
|View full text |Cite
|
Sign up to set email alerts
|

Soziale Phobie – eine im psychosomatischen Ambulanz- und Konsildienst unterdiagnostizierte Angsterkrankung?

Abstract: Social fears are common, whereas Social Phobia is diagnosed infrequently. Therefore, we compared the clinical diagnoses (ICD-10) in an outpatient and CL service of a psychosomatic university hospital to patients' self ratings in social fears on the Liebowitz Social Anxiety Scale (LSAS). Over the course of one year 688 patients could be characterized regarding their clinical diagnoses, LSAS-scores, symptom severity (SCL-90R) and psychosomatic complaints (GBB-24). Patients were assigned to three groups by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The reasons for the low specificity might be the relatively seldom (8.3%) clinical diagnosis of SAD (e.g. [ 8 ]) and the lack of a non-clinical comparison group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for the low specificity might be the relatively seldom (8.3%) clinical diagnosis of SAD (e.g. [ 8 ]) and the lack of a non-clinical comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis of social anxiety was used. Being aware of the relatively low number of diagnoses (8.3%, also see [ 8 ]) we additionally used internationally validated cut-offs of the LSAS as criteria [ 9 ]. A cut-off of 60 indicated a generalized social anxiety and a cut-off of 30 a social anxiety.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, service use rates do not fully reflect care and treatment of AD: A substantial fraction of individuals with AD are in contact with help services but present with other problems such as somatic or depressive symptoms (Asp et al 2020;Kirmayer et al 1993;Zimmerman and Chelminski 2003). It is reported that less than half of the potential generalized and social anxiety diagnoses are detected in primary and outpatient psychosomatic services (Wiltink et al 2010;Wittchen et al 2002). Consequently, only 30%-70% of service users with AD receive an anxiety-specific treatment (Fernández et al 2007;Roberge et al 2011;Stein et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, only a small percentage of those affected seek professional help [3]. In addition, SAD often goes unnoticed and is therefore underdiagnosed, even by professionals [31, 36]. Furthermore, CBT (cognitive behavior therapy), which shows the strongest evidence for treating childhood SAD [37], has a success rate of 70% [38].…”
Section: Introductionmentioning
confidence: 99%